Uji Aktivitas Antidiare Ekstrak Etanol Daun Ramania (Bouea macrophylla) Terhadap Mencit Betina Galur Swiss Webster - Aryzki, Saftia; Safitri, Ayu; Yesika, Yesika (Jurnal Farmasi & Sains Indonesia, 2024)
Diarrhea is still one of the leading causes of morbidity and mortality in almost all geographical regions of the world. All age groups are susceptible to diarrhea, but severe disease with high mortality is especially common among infants and children. In developing countries, children suffer from diarrhea more than 12 times per year and it accounts for 15 - 34 percent of all deaths. The ramania plant is green when young, and is often consumed as a salad or a mixture of ramania chili sauce. Ramania leaf extract contains several secondary metabolites, one of which is tannin, which has activity as antidiarrheal with the mechanism that the broken down tannate protein will bind to hydrolyzed tannin and pass through the intestine so that it can reduce the secretion of the small intestine and cause constipation. This research method is true experimental with pre-post test design with randomized control group design method with female Swiss Webster mice. The results suggest that the extract has met the parameters of simplisia standardization and extract standardization. The extract is proven to contain flavonoids, tannins, alkaloids, saponins, anthraquinones, phenolics, and terpenoids. Ramania leaf extract is proven to have antidiarrheal activity with a concentration of 400mg / kgBB against oleum ricini-induced mice based on the parameters of diarrhea onset time, decreased diarrhea frequency, and duration of diarrhea. Ethanol extract of ramania leaves at a dose of 400 mg/kgBB provides the best antidiarrheal activity against mice induced by oleum ricini.